2021
DOI: 10.1177/1098300721996084
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Launching Installation of Tiers 2 and 3 Systems of School-Wide Positive Behavioral Interventions and Supports

Abstract: The purpose of this longitudinal study was to examine patterns in implementation of Tier 2 and 3 school-wide positive behavioral interventions and supports (SWPBIS) systems to identify timings of installation that led to higher implementation of advanced tiers. Extant data from 776 schools in 27 states reporting on the first 3 years of Tier 2 implementation and 359 schools in 23 states reporting on the first year of Tier 3 implementation were analyzed. Using structural equation modeling, we found that higher T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The convergent validity analyses were completed using TFI scores from predominately elementary schools. Although it is common for the majority to be elementary schools, in part because there are more elementary schools in the United States than middle and high (Kittelman et al, 2022; McIntosh et al, 2018), the correlations between DSFI and TFI scores may be skewed toward district systems most supportive of PBIS implementation in elementary schools. For example, the Coaching subscale of the DSFI was significantly correlated only with Tier 1 and 2 implementation fidelity scores in this study; however, the majority of schools included in the study were elementary schools.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The convergent validity analyses were completed using TFI scores from predominately elementary schools. Although it is common for the majority to be elementary schools, in part because there are more elementary schools in the United States than middle and high (Kittelman et al, 2022; McIntosh et al, 2018), the correlations between DSFI and TFI scores may be skewed toward district systems most supportive of PBIS implementation in elementary schools. For example, the Coaching subscale of the DSFI was significantly correlated only with Tier 1 and 2 implementation fidelity scores in this study; however, the majority of schools included in the study were elementary schools.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a sample of 860 schools, McIntosh et al (2018) found teams who collected, summarized, and shared data in Year 1 was predictive of higher Tier 1 implementation fidelity scores in Year 3. Finally, using a sample of 776 schools, Kittelman et al (2022) demonstrated schools with higher Tier 1 implementation fidelity scores the year before implementing Tiers 2 and 3 had higher implementation fidelity scores in the first year of Tier 2 and 3 implementation.…”
Section: School and Practice Variables Predicting Implementation Of Pbismentioning
confidence: 97%
See 2 more Smart Citations
“…Given the myriad of student skills and outcomes related to SEL it is not surprising that schools have sought guidance on how to best support the social, emotional and academic development of students. One of the most widely implemented evidence-based frameworks is School-Wide Positive Behavior Interventions and Supports (SWPBIS) currently being implemented in over 27,000 US schools (Kittelman, Mercer, McIntosh, & Hoselton, 2021).…”
Section: Social-emotional Learning and Schoolsmentioning
confidence: 99%